Modifikasi Mesin Pencetak Pakan Budidaya Lele Berbentuk Pellet dengan Kebutuhan Daya Rendah - Leksono, Yudha Kristyanto; Setiyo, Yohanes -; Tika, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2014)
The aim of this study were to modify the machines with a small power requirements for printing fish feed pellets and to test the performance of the machine. The modified engine was a machine design by Giyarto result , modifications was on the power requirements . Stages of modification were calculate the strength of each major component of the engine , and followed by selecting the machine components . The main components of the machine are : V-belt, pulley, cylinder, cutting knife, pressing pellets and an electric motor. Engine performance testing conducted with 7 kg of dough pellets and the test was repeated 5 times. Parameters measured in this study were: machine capacity, efficiency and quality of the work machine. The results showed that the pellet-making machine modified increased in performance. The machine indicated the performance efficiency of an average 87.53 %
Keywords: Pellet, modification, efficiency and quality, performance